Marsirimpa as Core Cultural Value to Improve Social Value in Siponjot Village (Talenta Publisher, 2020)
Marsirimpa as a cultural, one of the traditional cultural, values ​​have been diminished from society by various daily activities that emphasize individual problems and individual solution. This condition does not only occur in urban areas, but also in rural areas which commonly hold a stronger value. In fact, Marsirimpa is a culture that important to overcome many obstacle in society life. The main aim of this community service is to empower the people within Siponjot Village. To be more specific, we aimed to empower Marsirimpa to foster social life within Siponjot Village. We had been held a form of Socialization has with the people of Siponjot Village, related to the transfer knowledge one of the socio-cultural values ​​that actually they already have (in the context of the Toba Batak community), namely the concept of marsirimpa, which can be used as motivation for cooperation or mutual cooperation, and explaining natural and environmental wealth as well as creative human resources owned by Siponjot village. As result, we reached a satsifiying result that the people is more enthusiasm and changes in social values ​​that support marsirimpa in everyday life.